PERSOALAN-PERSOALAN PEMBANGUNAN DAERAH (DIMENSI INSTITUSI DALAM SEKTOR PENGAIRAN DI KABUPATEN DAN KOTA TEGAL) - Irfan ' (JIP ( Jurnal Industri dan Perkotaan ), 2006)
Irrigation management using Dharma Tirta model in Tegal City and Regency ofCentral Java needs more advance institution alternative treatment. Empowerment of farmershows problematic situation. Local autonomy also needs strong leadership and vision topromote agricultural sector.